KEBIJAKAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. PERTAMINA REFINERY UNIT II DUMAI - MD, Herliana Rahmi; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
PT. Refinery Unit II Dumai as a refinery processing crude oil into Fuel Oil (BBM), Non-Fuel Oil and Petrochemicals has a commitment to assist the Government in developing the community around the Unit II Dumai refinery operation area through the Corporate Social Responsibility (CSR) Programme. In conducting the research, a descriptive qualitative approach with primary and secondary data collection techniques has been used through the unit of analysis at the nation state level, thus aiming to understand more deeply the influence of SDGs point 8 on the CSR of PT Pertamina Refinery Unit II Dumai. The results showed that there is a policy that becomes a reference to the Corporate Social Responsibility of PT Pertamina Refinery Unit II Dumai. So that it has various Corporate Social Responsibility (CSR) programmes that are implemented to provide benefits to the surrounding community and the environment. One of the CSR programmes implemented is a community development programme through economic empowerment. This programme aims to improve the welfare of the surrounding community through sustainable economic development, especially in SDGs point 8. Keywords: SDGs, CSR, Sustainable Economy, Economic Development